In situ growth of a ZnO nanowire network within a TiO(2) nanoparticle film for enhanced dye-sensitized solar cell performance - Bai, Yang (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.